FC1 Dipeptidyl peptidase IV inhibitors limit myocardial infarct size in a glucose-sensitive manner. Issue 17 (26th August 2010) - Hausenloy, D J; Wynne, A M; Theodorou, L; Mocanu, M M; Yellon, D M
Abstract : Rationale: The novel anti-diabetic agents, vildagliptin and sitagliptin, reduce blood glucose by augmenting endogenous levels of glucagon-like peptide (GLP-1), a substance which confers cardioprotection. They do this by inhibiting dipeptidyl peptidase (DPP) IV, the enzyme responsible for breaking down GLP-1. We hypothesised that DPPIV inhibitors might have cardioprotective effects. Methodology: Sprague–Dawley rats were given vildagliptin (oral gavage, 20 mg/kg/day), sitagliptin (oral gavage, 100 mg/kg/day), or control for 2 weeks. Excised hearts were then mounted on a Langendorff apparatus and perfused with buffer containing either 5 mmol/l or 11 mmol/l glucose and subjected to 35 min ischaemia/120 min reperfusion. Results: Vildagliptin pretreatment reduced myocardial infarct size in hearts perfused with buffer containing 11 mmol/l of glucose (34.4%±4.1% with vildagliptin vs 52.9%±5.2% with control: p<0.05:N>5/group) but not 5 mmol/l glucose (53.2%±4.8% with vildagliptin vs 52.6%±7.2% with control: p>0.05:N>5/group). The infarct-limiting effects were abolished in the presence of exendin9-39 (a GLP-1 receptor antagonist) and H-89 (a PKA antagonist) (61.5%±3.3% with vildagliptin+exendin9–39 and 59.4%±2.1% with vildagliptin+H-89 vs 35.0%±5.0% with vildagliptin+vehicle: p<0.05:N>5/group). Similarly, sitagliptin pretreatment reduced myocardial infarct size in hearts perfused with buffer containing 11 mmol/l of glucose (29.5%±5.1% with sitagliptin vs 52.9%±5.2% with control: p<0.05:N>5/group) but not 5 mmol/l glucose (44.4%±8.8% with sitagliptin vs 52.6%±7.2% with control: p>0.05:N>5/group). Again, the infarct-limiting effects were abolished in the presence of exendin9–39 (63.6%±5.5% with sitagliptin+exendin9–39 vs 30.1%±3.4% with sitagliptin+vehicle: p<0.05:N>5/group). Conclusions: Chronic treatment with the DPP-IV inhibitors reduced myocardial infarction via the GLP-1 receptor pathway and may also involve the PKA signalling pathway. Interestingly, this effect appears to be dependent on the blood glucose levels.